A comprehensive appraisal of Sharīʿah governance practices in Malaysian Islamic banks. Issue 3 (9th November 2020) - Naysary, Babak; Salleh, Marhanum Che Mohd; Abdullah, Nurdianawati Irwani
Abstract : Purpose: This study aims to empirically investigate the impact of the Sharīʿah Governance Framework (SGF) on improving Sharīʿah governance practices in Islamic banks in Malaysia and in addressing its related issues. Design/methodology/approach: Data collection was carried out using a comprehensive questionnaire survey, which was developed primarily based on SGF-2010 and arguments in the literature. The sample for this study includes key functionaries in Sharīʿah governance including senior managers, Sharīʿah committee (SC) and Sharīʿah team members of Islamic banks in Malaysia. Findings: The analysis of scores obtained from the questionnaire survey–including 41 items representing current significant issues in Sharīʿah governance–indicates that SGF-2010 has been successful in achieving its objectives and in addressing related issues. The results of the paired sample t -test show significant improvements in Sharīʿah governance practices in Malaysian Islamic banks in light of the aforementioned guideline by Bank Negara Malaysia. Research limitations/implications: Findings of this research suggest that among the five essential pillars of Sharīʿah governance, namely, accountability and responsibility, independence, competence, confidentiality and transparency, most of the improvements and changes brought about by SGF-2010 are attributable to accountability and responsibility. However, there is still room for improvement in other components of the SGF, particularly with regard to transparency and the independence of the SC and Sharīʿah team. Originality/value: Given the importance of Sharīʿah governance and considering recent endeavours to improve Sharīʿah-compliant culture among Islamic banks in Malaysia, this research is among the first attempts to empirically and comprehensively delve into this subject and evaluate its main issues by directly contacting key players in the Islamic banking industry and providing first-hand highlights. This research also compares the findings based on SGF-2010 with the requirements of SGF-2017 and Sharīʿah Governance Policy Document (SGPD-2019), which were released after this research was completed, where applicable.